Analysis of the Impact of High Inflation on Present Value Calculation in Investment in Indonesia - Azzahra, Syanna Nabila; Widiana, Fani Almira; Azzahra, Fathimah (International Journal of Quantitative Research and Modeling, 2024)
Inflation is a crucial economic indicator that significantly impacts investment decisions. In Indonesia, inflation has shown substantial fluctuations due to factors such as global commodity prices, monetary policy, and domestic demand. This study aims to analyze the impact of high inflation on present value (PV) calculations in investment contexts, particularly in long-term projects. Present value, a method for assessing future cash flows based on their current value, is influenced by the discount rate, which tends to rise with inflation. Using data from 20152023, this research compares two inflation scenarios (1.56% and 6.38%) and calculates the PV of an investment with a future value of IDR 1,000,000 over 5 years. The results show a significant decrease in PV under high inflation, from IDR 925,497 to IDR 733,999, indicating that inflation erodes the purchasing power of future cash flows. Furthermore, the analysis highlights the more significant impact of inflation on sectors with higher cash flow projections, such as infrastructure. The study underscores the need for investors to consider inflation when making investment decisions to manage risks and maximize returns.